1994
DOI: 10.1002/bjs.1800810711
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygen saturation, transcranial Doppler ultrasonography and stump pressure in carotid surgery

Abstract: Transcranial Doppler ultrasonography (TCD) of the middle cerebral artery (MCA), light-reflective cerebral oximetry and measurement of internal carotid artery stump pressure were compared as methods of monitoring cerebral perfusion during carotid surgery in 33 patients. Median cerebral oxygen saturation was 70 (range 62-85) per cent and TCD-measured mean blood velocity 42 (range 19-91) cm/s before carotid cross-clamping, falling to 68 (53-83) per cent and 16 (0-50) cm/s respectively on application of the clamps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 23 publications
1
28
0
2
Order By: Relevance
“…Cerebral NIRS has been shown to track changes in jugular venous bulb saturation in healthy volunteers under conditions of hypoxia (27) and has also been validated compared with PET scanning, with 133 Xe washout methods, and with internal carotid artery stump pressures (46). Previous studies have shown that change in NIRS provides a good measure of the proportion of blood that is oxygenated; it does not, however, distinguish how much blood is in the arterial or venous part of the vascular bed (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral NIRS has been shown to track changes in jugular venous bulb saturation in healthy volunteers under conditions of hypoxia (27) and has also been validated compared with PET scanning, with 133 Xe washout methods, and with internal carotid artery stump pressures (46). Previous studies have shown that change in NIRS provides a good measure of the proportion of blood that is oxygenated; it does not, however, distinguish how much blood is in the arterial or venous part of the vascular bed (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the human brain, however, NIRS-determined capillary oxygenation is functionally related to the balance between arterial and internal jugular venous oxygen saturation (34). Cerebral NIRS has been shown to track changes in jugular venous bulb saturation in healthy volunteers under conditions of isocapnic hypoxia (24) and has also been validated compared with positron emission tomography scanning (37), with 133 Xe washout methods (39), and with internal carotid artery stump pressures (47). Moreover, a recent report indicates that de- Fig.…”
Section: Differential Alterations In Cerebral and Muscle Oxygenation mentioning
confidence: 99%
“…TCD is a widespread inexpensive tool that can detect intracranial stenoses, occlusions, collaterals, microemboli, hypoperfusion, and hyperperfusion in extracranial carotid revascularization procedures and in acute stroke patients. [7][8][9][10][11][12][13][14] TCD monitoring head frames are radiolucent, with only transducers and knob-locks leaving recognizable small imprints on subtracted angiographic images. These radio-opaque parts can be removed or placed out of plane for standard projections, making application of TCD monitoring feasible during IA reperfusion procedures.…”
mentioning
confidence: 99%
“…ТКДГ является широко распространенным недорогим методом, позволяющим обнаруживать стенозы, окклюзии, наличие коллате-ралей, регистрировать микроэмболы во внутричереп-ных артериях, определять зоны гипо-и гиперперфузии при проведении экстракраниальной реваскуляризации сонных артерий и у пациентов с острым инсультом [7][8][9][10][11][12][13][14]. Головные устройства для проведения ТКДГ-мониторинга пропускают рентгеновское излучение, только передатчики и ручки-замки оставляют неболь-шой узнаваемый след на изображениях субтракци-онной ангиографии.…”
unclassified